2006
DOI: 10.1080/00480169.2006.36596
|View full text |Cite
|
Sign up to set email alerts
|

The role of surgery in the management of canine anal furunculosis. A review of the literature and a retrospective evaluation of treatment by surgical resection in 51 dogs

Abstract: The aetiopathogenesis of canine AF remains unclear. Whilst recent advances in medical management by the use of various immunomodulatory medications (such as cyclosporine) hold promise, this approach has yet to be refined with respect to affordability, long-term efficacy and morbidity. With meticulous surgical dissection and reconstruction techniques (anoplasty), excellent success rates can be achieved following a single surgical procedure with minimal complications. Surgery remains a viable treatment option, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Two of the dogs in this study underwent anal sacculectomy as part of a management strategy for ongoing AF as has been recommended (Milner ). Both dogs had very mild AF lesions but which involved the anal sacs and surgical intervention was limited to routine closed anal sacculectomy following a period of medical management involving low‐dose prednisolone therapy (one dog) or cyclosporine therapy (one dog).…”
Section: Discussionmentioning
confidence: 99%
“…Two of the dogs in this study underwent anal sacculectomy as part of a management strategy for ongoing AF as has been recommended (Milner ). Both dogs had very mild AF lesions but which involved the anal sacs and surgical intervention was limited to routine closed anal sacculectomy following a period of medical management involving low‐dose prednisolone therapy (one dog) or cyclosporine therapy (one dog).…”
Section: Discussionmentioning
confidence: 99%
“…Many treatments, including both medical and surgical approaches (7), have been tried with varying degrees of outcome and efficacy. However, recent studies have shown the clinical benefit of immunomodulatory therapy with ciclosporin and other immunomodulatory drugs such as azathioprine (8–10).…”
Section: Introductionmentioning
confidence: 99%
“…Although satisfactory short-term results are often achieved through surgical intervention (up to 80% of dogs improve), lesions redevelop in a high proportion (50% to 90%) of affected dogs, with complications including fecal incontinence or rectal stricture. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Perianal sinuses reportedly respond to immunosuppressive treatment protocols, which supports the hypothesis that the disease is immune mediated. 7,8,13,[15][16][17][18][19][20][21][22] Administration of prednisone at a high dose (2 mg/kg [0.91 mg/lb], PO, q 24 h for 2 weeks, followed by 1 mg/kg [0.45 mg/lb], PO, q 24 h for 4 weeks) and feeding of a novel-protein diet (ie, diet including protein to which dogs had not previously been exposed) resulted in short-term improvement or cure in 67% of dogs with perianal sinuses and concurrent colitis in 1 study.…”
mentioning
confidence: 79%
“…These findings underscore the importance of thorough examination of the affected anal area at the time of initial examination and recommendation of anal sacculectomy should anal sacs be involved in the perianal sinuses. 19,35 The anal sacs of German Shepherd Dogs are located deeper within the perianal tissue, and they extend further cranially into the external anal sphincter than in other breeds. 10 Therefore, a meticulous technique and good anatomic knowledge are needed to ensure complete anal sacculectomy in German Shepherd Dogs, with minimal adverse sequelae.…”
Section: Discussionmentioning
confidence: 99%